Analisis Bioinformatika GenblaCTX-M Pengkode β-Laktamase Spektrum Luas pada Klebsiella pneumoniae Menggunakan Data GenBank NCBI - Dwi Sakila Ulfa; Gusti Ayu Niscari Dewi; Ira Firati Fionita; Faturrahman; Sarkono (Journal of Microbiology, Biotechnology and Conservation, 2026)
Klebsiella pneumoniae is a short rod-shaped Gram-negative bacterium capable of fermenting lactose and various other carbohydrates, producing acid and gas. The blaCTX-M gene is one of the major genes responsible for β-lactam resistance in K. pneumoniae. This study aimed to analyze the genetic variation and phylogenetic relationships of the blaCTX-M gene in K. pneumoniae using nucleotide sequence data retrieved from the NCBI GenBank database. A total of 19 sequences representing isolates from different countries were aligned to identify nucleotide variations. The alignment results revealed genetic variation among the isolates, with most forming a closely related cluster indicating high sequence similarity. Eighteen isolates showed identical characteristics with minor variations, while one isolate, NG_048898, exhibited the highest number of nucleotide variations. A total of 168 nucleotide variations were identified, predominantly nonsynonymous substitutions, distributed throughout the nucleotide sequence. Phylogenetic analysis using the Neighbor-Joining method with the Kimura 2-parameter model supported the alignment results, showing a distinct branch for isolate NG_048898, suggesting a different evolutionary origin. These findings highlight the genetic diversity of the blaCTX-M gene in K. pneumoniae isolates and provide important insights into the distribution of β-lactamase genes, which are essential for understanding antibiotic resistance patterns.